2020
DOI: 10.3389/fnins.2020.00458
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Molecule L1 Agonist Mimetics Protect Against the Pesticide Paraquat-Induced Locomotor Deficits and Biochemical Alterations in Zebrafish

Abstract: Besides several endogenous elements, exogenous factors, including exposure to pesticides, have been recognized as putative factors contributing to the onset and development of neurodegenerative diseases, including Parkinson's disease (PD). Considering the availability, success rate, and limitations associated with the current arsenals to fight PD, there is an unmet need for novel therapeutic interventions. Therefore, based on the previously reported beneficial functions of the L1 cell adhesion molecule, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 141 publications
2
16
0
Order By: Relevance
“…Behavioral-wise, paraquat reduces locomotor activity of zebrafish, indicated by decreased swimming distance and velocity ( Wang et al, 2018 ). This finding agrees with Joseph et al (2020) , who documented an increase in the number of freezing bouts and freezing durations of zebrafish after paraquat administration. Moreover, the same study also found that paraquat impairs the process of acquiring and consolidating spatial memory.…”
Section: Zebrafish As a Model Of Parkinson’s Diseasesupporting
confidence: 92%
See 3 more Smart Citations
“…Behavioral-wise, paraquat reduces locomotor activity of zebrafish, indicated by decreased swimming distance and velocity ( Wang et al, 2018 ). This finding agrees with Joseph et al (2020) , who documented an increase in the number of freezing bouts and freezing durations of zebrafish after paraquat administration. Moreover, the same study also found that paraquat impairs the process of acquiring and consolidating spatial memory.…”
Section: Zebrafish As a Model Of Parkinson’s Diseasesupporting
confidence: 92%
“…Redox imbalance caused by the increased mitochondrial ROS production causes oxidative stress and damages mitochondrial respiration (Bastías-Candia et al, 2019). Supporting this, Joseph et al (2020) reported that paraquat exposure to zebrafish larvae reduced mitochondrial viability and obstructed the production of ATP. Interestingly, paraquat is also found to activate nuclear factor-kappa B (NFκB) that results in DNA fragmentation and TLR4/NFκB-mediated neuroinflammation (Feng et al, 2019;.…”
Section: Paraquatmentioning
confidence: 88%
See 2 more Smart Citations
“…14,17 L1 mimetics stimulated repair not only in mice but also in zebrafish, where they improved recovery after spinal cord injury, 16 remyelination after demyelination (Hae-Chul Park, personal communication), and resistance to a pesticide. 47 Three L1 mimetic compounds, one of them (duloxetine) FDA approved, indeed, enhanced neuronal migration and survival, neurite outgrowth of cerebellar neurons, and process formation of Schwann cells in cell culture. In a previous study, we have shown that the L1 mimetic compounds also stimulate neurite outgrowth from spinal motor neurons, dorsal root ganglion neurons and cortical neurons as well as proliferation and migration of Schwann cells and in vitro myelination.…”
Section: Discussionmentioning
confidence: 99%